Murine Butyrophilin-Like 1 and Btnl6 Form Heteromeric Complexes in Small Intestinal Epithelial Cells and Promote Proliferation of Local T Lymphocytes - Lebrero-Fernández, Cristina; Bergström, Joakim H.; Pelaseyed, Thaher; Bas-Forsberg, Anna (Frontiers in Immunology, 2016)
To date, few molecular conduits mediating the cross-talk between intestinal epithelial cells and intraepithelial lymphocytes (IELs) have been described. We recently showed that Butyrophilin-like (Btnl) 1 can attenuate the epithelial response to activated IELs, resulting in reduced production of pro-inflammatory mediators such as IL-6 and CXCL1. We here report that like Btnl1, murine Btnl6 expression is primarily confined to the intestinal epithelium. Although Btnl1 can exist in a cell surface-expressed homomeric form, we found that it additionally forms heteromeric complexes with Btnl6, and that the engagement of Btnl1 is a prerequisite for surface expression of Btnl6 on intestinal epithelial cells. In an IEL-epithelial cell co-culture system, enforced epithelial cell expression of Btnl1 significantly enhanced the proliferation of IELs in the absence of exogenous activation. The effect on proliferation was dependent on the presence of IL-2 or IL-15 and restricted to IELs upregulating CD25. In the gamma delta (gd) T-cell subset, the Btnl1-Btnl6 complex, but not Btnl1, specifically elevated the proliferation of IELs bearing the Vg7Vd4 receptor. Thus, our results show that murine epithelial cell-specific Btnl proteins can form intrafamily heterocomplexes, and suggest that the interaction between Btnl proteins and IELs regulates the expansion of IELs in the intestinal mucosa.